Innovations, ICT and ICT‐driven labour productivity in Poland1: A firm level approach. Issue 4 (1st September 2017) - Arendt, Lukasz; Grabowski, Wojciech
Abstract: In this paper, we describe and develop a two‐step model, based on the CDM approach and the new firm paradigm, to link innovation outputs and ICT to productivity gains, using micro‐level data from 1, 000 Polish companies. Our study confirmed the mediating role of innovations and ICT complementarities with respect to productivity gains. However, the main finding is that the strength of this relationship depends on the company's distance to the technological frontier. We show that the more productive a company is, the more important are co‐innovative sources of productivity. Thus, support programmes should also be provided to highly productive companies, which require a higher level of ICT complementarities to boost productivity. This finding may hold true for other CEE countries as well.